Assessment of thermal necrosis risk regions for different bone qualities as a function of drilling parameters. (August 2018) - Chen, Yung-Chuan; Tu, Yuan-Kun; Tsai, Yi-Jung; Tsai, Yi-Shan; Yen, Cheng-Yo; Yang, Shih-Chieh; Hsiao, Chih-Kun
Highlights: Risk region of thermal necrosis regions during bone drilling were evaluated. The 3D dynamic FE model can effectively simulate the bone temperature elevation during drilling. Bone temperature increased as the bone density and drill-bit diameter. Increasing the drill speed and feeding force could reduce the thermal necrosis regions. Abstract: Background and objective: During bone drilling, the heat generated by friction depends directly on bone quality and surgical parameters. Excessive bone temperatures may cause thermal necrosis around the pilot hole, weaken the purchase of inserted screws, and in turn reduce the stability of screw fixation. A few studies have addressed the key parameters of drilling, such as the rotation speed of the drill-bit, feed force (axial force), feed rate, tool type, and tip geometry of drill-bits. Nevertheless, in the literature, information on the relationship between bone quality and thermally affected regions is still lacking. This study employed a three-dimensional dynamic elastoplastic finite element model to evaluate the influence of surgical parameters on the bone temperature elevation and assess the risk region of thermal necrosis for different bone qualities as a function of drilling parameters. Methods: To ascertain the heat generation rate and the high-risk region of thermal necrosis, the effects of bone quality, feed rate, feed force, and drill-bit diameter on the bone temperature elevation were explained using a three-dimensional dynamic elastoplastic finite element model, which was validated through experimental measurements. Results: The bone temperature was affected by the drilling parameters; the maximum temperature was attained at the junction of cancellous and cortical bones. The bone temperature increased with cortical bone thickness, bone density, and drill-bit diameter, and it decreased with the drilling speed and feed force. Conclusions: The present model could assess the risk region of thermal necrosis by accurately analyzing the bone temperature elevation for various bone qualities, feed forces, and feed rates. The bone temperature increased with the bone mineral density and cortical bone thickness. The highest bone temperature and maximum necrosis region were found near the junction of cortical and cancellous bones. Increasing the drilling speed or feed force can minimize the bone temperature elevation and the risk range of thermal necrosis.